A Historical Exploration of Islamic Discourse in Sri Lanka: A Descriptive Analysis of Contemporary Da’wah Organizations - Aroos , Ashker; Ashath , Mohamed; Ghous , Mohammed Insaf Mohammed (At-Tajdid - Intellectual Refereed Journal, 2025)
The Islamic discourse in Sri Lanka, which has a history of more than a thousand years, has been questioned recently. Following the Easter attack in 2019, the work of contemporary Islamic organizations has been viewed with suspicion by others. This has necessitated an explanation of the history of Islamic discourse in Sri Lanka. A study of the origin, development, and contemporary status of Islamic organizations, which are considered to be the contemporary ambassadors of Islam, is required. For this, qualitative research based on the library and relevant authentic sources has been used as the research method. This study begins with a brief historical introduction to the Muslims of Sri Lanka. Then, in a two-part discussion, the Ṣūfī orders, Islamic scholars and individuals, Islamic Educational Institutions, Islamic Da’wah organizations, etc. that have supported the development of Islam in Sri Lanka are explained in historical order. In the second part, the selected Islamic Da’wah organizations carrying out Islamic discourse in contemporary Sri Lanka such as Tabligh Jamaat, Jamaati-Islami, and Jamaati-Tawheed are examined. Finally, this study attempts to record the history of Islamic discourse in Sri Lanka descriptively from past to up to date. Keywords: Historical Exploration, Islamic Discourse, Descriptive Analysis, Da’wah Organizations, Sri Lanka.